2000
DOI: 10.1590/s0100-40422000000500010
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenos da resina de Protium heptaphyllum March (B0urseraceae): caracterização em misturas binárias

Abstract: Recebido em 20/7/99; aceito em 8/1/00 TRITERPENES FROM THE RESIN OF PROTIUM HEPTAPHYLLUM MARCH (BURSERACEAE):CHARACTERIZATION IN BINARY MIXTURES. Eight triterpenes, maniladiol, breine, ursa-9(11):12-dien-3β-ol, oleana-9(11):12-dien-3β-ol, 3α-hydroxy-tirucalla-8,24-dien-21-oic acid, 3α-hydroxy-tirucalla-7,24-dien-21-oic, α and β amyrines were isolated as binary mixtures obtained from the chloroform extract of the oil-resin of Protium heptaphyllum March. The identification of the compounds was based mainly in 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 5 publications
2
24
0
10
Order By: Relevance
“…Repeated silica gel and Sephadex LH-20 column chromatography of the active extracts of P. guajava afforded a mixture of flavonoids (1), triterpenes (2) and sterol (3). The triterpene (α and β-amyrin) (Maia et al, 2000) and sterol (β-sitosterol) (Goular et al, 1993) were identified by direct comparisons (TLC, UV, 1 H and 13 C NMR) with authentic samples available in our laboratory. The flavonoids group (1) could be easily detected by spraying the TLC plates with NP/PEG (natural products-polyethylenglycol reagent) showing yellow colour for a monohydroxylated systems in B ring (Wagner et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Repeated silica gel and Sephadex LH-20 column chromatography of the active extracts of P. guajava afforded a mixture of flavonoids (1), triterpenes (2) and sterol (3). The triterpene (α and β-amyrin) (Maia et al, 2000) and sterol (β-sitosterol) (Goular et al, 1993) were identified by direct comparisons (TLC, UV, 1 H and 13 C NMR) with authentic samples available in our laboratory. The flavonoids group (1) could be easily detected by spraying the TLC plates with NP/PEG (natural products-polyethylenglycol reagent) showing yellow colour for a monohydroxylated systems in B ring (Wagner et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Alguns gêneros da família Burseraceae (Elaphrium, Icica, Canarium e Protium) são produtoras de resina. Estas resinas são conhecidas genericamente como elemi e encerram em sua composição triterpenóides tetracíclicos, os ácidos elemadienólico e elemadienóico, mas principalmente triterpenóides pentacíclicos, tais como a mistura α-e β-amirina, o maniladiol e a breína (Maia et al, 2000;Costa, 1996).…”
Section: Introductionunclassified
“…O gênero Protium é amplamente encontrado na região amazônica, onde suas óleo-resinas são popularmente conhecidas como "breus" [31][32][33][34].…”
Section: -Protium Sppunclassified
“…Na medicina popular é considerada um importante agente terapêutico, sendo utilizada como antiinflamatório, analgésico, expectorante e cicatrizante [31][32].…”
Section: -Protium Sppunclassified
See 1 more Smart Citation